The number of solutions of cubic equations over Q3 - Mansoor Saburov; Mohd Ali Khameini Ahmad (Universiti Kebangsaan Malaysia, 2015)
We provide the number of solutions of a cubic equation in domains , 3 \ , 3\ 3 and Q3.